2021
DOI: 10.1093/nar/gkab105
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of spacer acquisition by sequential assembly of the adaptation module in Synechocystis

Abstract: CRISPR–Cas immune systems process and integrate short fragments of DNA from new invaders as spacers into the host CRISPR locus to establish molecular memory of prior infection, which is also known as adaptation in the field. Some CRISPR–Cas systems rely on Cas1 and Cas2 to complete the adaptation process, which has been characterized in a few systems. In contrast, many other CRISPR–Cas systems require an additional factor of Cas4 for efficient adaptation, the mechanism of which remains less understood. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Cas1 and Cas2 interact to form an integrase complex ( 23 , 25 , 28 ) found to be essential for acquiring new spacers in all adaptation-competent CRISPR-Cas systems tested thus far ( 23 , 24 , 26–28 , 31 , 32 , 48 , 100 ). Many systems also require additional Cas proteins in order to adapt.…”
Section: Discussionmentioning
confidence: 99%
“…Cas1 and Cas2 interact to form an integrase complex ( 23 , 25 , 28 ) found to be essential for acquiring new spacers in all adaptation-competent CRISPR-Cas systems tested thus far ( 23 , 24 , 26–28 , 31 , 32 , 48 , 100 ). Many systems also require additional Cas proteins in order to adapt.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Notably, the above two CRISPR-Cas systems both lack Cas4. In contrast, in the three available Cas1-Cas2-prespacer structures of Cas4-containing CRISPR-Cas systems ( E. faecalis , 21 Synechocystis , 22 and Geobacter sulfurreducens 10 ), the Cas2 dimers were all oriented perpendicular to the axis of the prespacer ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 92%
“…The overall architecture of the S. thermophilus Cas1-Cas2-prespacer complex was similar to that of previous Cas1-Cas2-prespacer structures. 3 , 10 , 21 , 22
Figure 2 Cryo-EM structure of the S. thermophilus Cas1-Cas2-prespacer complex (A) Schematic diagram of the prespacer DNA, including a 23-bp duplex and two 15-nt 3′ overhangs on both ends. The PAM-containing and PAM-deficient overhangs are colored red and blue, respectively.
…”
Section: Resultsmentioning
confidence: 99%
“… 41 For example, in type I-C and I-D, one Cas4 protein interacts with a Cas1 dimer. 14 , 48 Therefore, the spacer trimming effects might be specific to systems with unfused, stand-alone Cas4 proteins. However, even though the effects of spacer trimming by Cas4/1 from V-B was not observed in this study, we cannot exclude a role for Cas4/1 in prespacer processing, as observed in other Cas4/1 systems.…”
Section: Discussionmentioning
confidence: 99%